Prevention of neuronal damage in brains of chronic stress‑induced male Wistar rats administering Centella Asiatica (L) urban - Jagadeesan, Saravanan; Gopalakrishna, Prarthana Kalerammana; Sura, Sreenivasulu; Karikalan, Barani; Dandala, Krishna Chaitanya Reddy; Ravindranadh, Gandrakota; Mohd Moklas, Mohamad Aris; Vishnumukkala, Thirupathirao (Wolters Kluwer Medknow Publications, 2024)
Introduction: Physiological and psychological response of an organism to repetitive stimulus leads to chronic stress which results in depression. This affects the neuro‑endocrine axis causing hypersecretion of glucocorticoids which damages the hippocampal neurons in brain through oxidative stress. The body responds by producing Catalase (CAT) an antioxidant found on peroxisomes, which splits the hydrogen peroxide produced by oxidative stress into water and oxygen which are nontoxic, thus offering a protective effect. The synaptic function of the hippocampal neurons is dependent on acetylcholinesterase (AChE) and oxidative stress affects the levels of AChE. The available anti‑depressants have the late onset of action and increased toxicity. Centella asiatica (CA), an herb with neuroprotective properties, is known as neuro‑tonic and has less toxicity and has been used in ancient traditional medicines. This study aims to examine the neuroprotective effects of crude extract of CA on hippocampal neurons using Nissls stain and levels of AChE and expression of mRNA CAT in the brain tissues of chronic unpredictable mild stress (CUMS)‑induced male Wistar rats. Materials and Methods: Thirty‑six Male Wistar rats aged 8–10 weeks were held in six groups. One group assigned as control, whereas the other groups were administered CUMS by various stressors, namely restrain, forced swimming in cold water, overnight food and water deprivation, wet bedding, cage tilt at 45°, tail pinching, overcrowding the cages, and change of cage mates randomly for a period of 64 days. One of the stress‑induced groups was retained as model group and others were administered crude extracts of CA at the doses of 200, 400, 800, and fluoxetine (Flx) 10 mg/kg body weight. At the end of 64 days, the rats were euthanized and the brain tissue was collected for Nissls staining of the hippocampus, measure levels of AChE using ELISA and expression of mRNA CAT levels using RT‑PCR. Results: The rats of the model group exhibited reduced number of viable neurons in the hippocampus as observed in Nissls stain, reduced levels of AChE, and reduced expression of mRNA CAT in the brain tissue while the rat groups receiving CA showed increase in the number of viable neurons, increase in level of AChE, and increase in the expression of mRNA CAT in the brain tissues. The results were comparable to that of Flx. Conclusion: CA effectively attenuates CUMS‑induced neuronal loss in the hippocampus of the rat’s brain, normalizes AChE levels, and also the expression of mRNA CAT antioxidant levels. CA could be used in the long‑term prevention of chronic stress‑induced depression.